2021
DOI: 10.3390/app11209377
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Investigations on the Performance of Micro Steel Fibres in Ultra-High-Performance Concrete under Monotonic and Cyclic Tensile Loading

Abstract: : Ultra-high-performance fibre-reinforced concrete (UHPFRC) can preferably be used for lean and thin-walled structures due to its very high compressive strength. Based on the adverse relation between the increased load bearing capacities and the condensed dead weight of UHPFRC-structures, the impact of live loads in the design gets bigger and, in case of traffic loads, the effects of a cyclic loading have to be considered in more detail. In this context, this study investigated the material behaviour of UHPFRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…The high-strength micro steel fibre is 13.0 mm in length and 0.19 mm in diameter. That gives a slenderness ratio according to Equation (1). The tensile strength is more than 2000 N/mm 2 and the Young's modulus around 200,000 N/mm 2 , according to the manufacturer's data.…”
Section: High-strength Micro Steel Fibre Test Specimen and Test Progr...mentioning
confidence: 89%
See 2 more Smart Citations
“…The high-strength micro steel fibre is 13.0 mm in length and 0.19 mm in diameter. That gives a slenderness ratio according to Equation (1). The tensile strength is more than 2000 N/mm 2 and the Young's modulus around 200,000 N/mm 2 , according to the manufacturer's data.…”
Section: High-strength Micro Steel Fibre Test Specimen and Test Progr...mentioning
confidence: 89%
“…The intended softening respectively ductile material behaviour of fibre concretes can only be achieved, if the tested fibre design leads to fibre pullout instead of fibre rupture [1,2]. Therefore, the fibres have to match to the strength properties of the concrete.…”
Section: State Of the Art Of Fibre Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations during the test execution showed that there are two failure mechanisms for pullout tests under cyclic tensile loading: Fibre pullout and fibre rupture [ 25 ]. These two failure mechanisms depend on the orientation of the fibres.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…In literature, steel fibre reinforced concrete is usually investigated in uniaxial compression and tensile tests, e.g. [12,13], as well as in flexural tests, e.g. [9,14], with regard to the secondary creep rate.…”
Section: Introduction and State Of The Artmentioning
confidence: 99%